Conductive nano calcium carbonate and preparation method thereof
By designing a multi-layer composite structure in conductive nano calcium carbonate, using layer-layer assembly technology and in-situ doping and coating technology, the problems of insufficient conductivity, uniformity and stability are solved, and high-performance and environmentally friendly production of conductive nano calcium carbonate are achieved.
Patent Information
- Application Number
- CN202411737314.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-07
AI Technical Summary
The existing conductive nano calcium carbonate materials have shortcomings in terms of conductivity, uniformity and stability. Especially in the design of multi-layer composite structures, it is difficult to achieve close bonding between the conductive layer and the substrate, resulting in unstable conductive properties.
By designing conductive nano-calcium carbonate of multi-layer composite structures and using layer-layer assembly technology, the uniform combination of the polyelectrolyte modified layer and the conductive tin doped indium oxide layer is achieved, enhancing the conductivity and dispersion of the material.
It significantly improves the conductive properties and stability of the materials, enhances its potential in electronic industry applications, and reduces environmental risks in the production process, achieving the dual goals of high performance and environmental protection.
Smart Images

Figure CN119570290A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano materials, in particular to conductive nano calcium carbonate and a preparation method thereof. Background Art
[0002] With the rapid development of the electronics industry, sensor technology and smart materials, the demand for new materials with excellent physical and chemical properties and good electrical conductivity is growing. Nano calcium carbonate has been widely used in many fields due to its good mechanical strength, thermal stability, biocompatibility and low cost. However, traditional nano calcium carbonate does not have electrical conductivity, which limits its application in specific occasions. Therefore, the development of a new material that maintains the original advantages of nano calcium carbonate and has good electrical conductivity has become one of the current research focuses.
[0003] At present, the existing conductive nano-calcium carbonate materials improve their conductivity by doping conductive elements. However, this simple doping method often leads to poor uniformity and dispersion of the material, which in turn affects its overall performance. Secondly, the doping process may introduce impurities, reduce the purity and stability of the material. Especially for the design of multi-layer composite structures, the existing technology is difficult to achieve a close bond between the conductive layer and the substrate, resulting in unstable conductive performance, and it is difficult to accurately control the thickness and distribution of the conductive layer.
[0004] In summary, the existing conductive nano-calcium carbonate materials have deficiencies in conductivity, uniformity and stability. Therefore, it is particularly important to develop a conductive nano-calcium carbonate material with a multilayer composite structure and an efficient and environmentally friendly preparation method thereof to overcome the above problems. Summary of the invention
[0005] The purpose of the present invention is to make up for the deficiencies of the prior art and provide a conductive nano calcium carbonate and a preparation method thereof. The conductive nano calcium carbonate can be designed with a multi-layer composite structure to significantly improve the conductive performance and stability of the material. The layer-by-layer assembly technology is used to achieve a uniform combination of a polyelectrolyte modified layer and a conductive tin-doped indium oxide layer, thereby enhancing the conductivity and dispersibility of the material. This structural design not only improves the application potential of the material in the electronics industry, but also reduces the environmental risks in the production process, thereby achieving the dual goals of high performance and environmental protection.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: On the one hand, the conductive nano calcium carbonate has a multi-layer composite structure, including a nano calcium carbonate matrix, a polyelectrolyte modified layer located on the surface of the matrix, and a conductive tin-doped indium oxide layer coated on the modified layer, specifically:
[0007] The polyelectrolyte modified layer is formed by assembling positively charged chitosan and negatively charged PSS polyelectrolyte on the surface of the nano calcium carbonate matrix, wherein:
[0008] The positively charged chitosan is selected to have a deacetylation degree of 80%-95%, the pH value of the nano-calcium carbonate dispersion is adjusted and the chitosan solution is added, so that the chitosan is uniformly adsorbed on the surface of the nano-calcium carbonate matrix through electrostatic attraction to form a preliminary modified layer;
[0009] After the chitosan is adsorbed, the negatively charged PSS polyelectrolyte solution is added to the reaction system to allow the PSS and chitosan to undergo electrostatic recombination, and the layer-by-layer assembly cycle operation is repeated 2-4 times to allow the PSS and chitosan to be alternately adsorbed to form a multi-layer polyelectrolyte modified layer;
[0010] The conductive tin-doped indium oxide layer dissolves soluble tin chloride and indium chloride and reacts with the nano-calcium carbonate suspension to form a uniform conductive layer.
[0011] Furthermore, the concentration of the positively charged chitosan during the assembly process is controlled at 0.03-0.08 mol / L, and the pH value of the nano-calcium carbonate dispersion is adjusted to 4.5-5.5. After the chitosan solution is added, stirring is performed at a temperature of 40-60° C. for 1.5-2.5 hours.
[0012] Furthermore, the concentration of the negatively charged PSS polyelectrolyte solution is controlled at 0.02-0.06 mol / L and stirred at a temperature range of 40-60° C. for 1-2 hours.
[0013] Furthermore, the conductive tin-doped indium oxide layer is composed of tin ions Sn 2+ and indium ions In 3 With oxygen ions O 2- The tin-doped indium oxide ITO generated by the reaction has a molar ratio of tin ions to indium ions of 1:8-1:12, a mass ratio of tin ions to nano-calcium carbonate of 0.05-0.15:1, and a mass ratio of indium ions to nano-calcium carbonate of 0.5-1.5:1.
[0014] On the other hand, the preparation method of conductive nano calcium carbonate, the specific steps of the preparation method are:
[0015] S1. Pretreatment of nano calcium carbonate matrix: using nano calcium carbonate as raw material, placing the nano calcium carbonate raw material in a high-speed disperser, adding deionized water as a dispersion medium for stirring and dispersion, so that the nano calcium carbonate is initially dispersed to form a suspension;
[0016] S2, ultrasonic treatment: the suspension after preliminary dispersion is transferred to an ultrasonic cleaner, and ultrasonically treated for 30-60 minutes at an ultrasonic frequency of 20-40kHz to break up the agglomerated nano-calcium carbonate particles to obtain a uniformly dispersed nano-calcium carbonate suspension, and the suspension after ultrasonic treatment is filtered, and the filter cake is washed with deionized water for multiple times to obtain a pre-treated nano-calcium carbonate dispersion;
[0017] S3, polyelectrolyte modified layer assembly: adding sodium hydroxide solution to the pretreated nano-calcium carbonate dispersion to adjust the pH value of the dispersion to 4.5-5.5, and adding chitosan solution to make the chitosan solution uniformly dispersed in the nano-calcium carbonate suspension;
[0018] S4, PSS adsorption and layer-by-layer assembly cycle: After the chitosan adsorption is completed, the PSS polyelectrolyte solution is added dropwise, and stirring is continued during the dropping process. After the dropping is completed, stirring and reacting at 40-60°C for 1-2 hours to allow PSS and chitosan to undergo electrostatic compounding. The layer-by-layer assembly cycle operation is repeated 2-4 times to finally obtain a polyelectrolyte-modified nano-calcium carbonate suspension;
[0019] S5, in-situ doping and coating of the conductive tin-doped indium oxide layer: the nano-calcium carbonate suspension modified by the polyelectrolyte is subjected to metal ion adsorption, and soluble tin chloride and indium chloride are dissolved in deionized water in a ratio of 0.05-0.15:1 of tin ions to nano-calcium carbonate and 0.5-1.5:1 of indium ions to nano-calcium carbonate to prepare a mixed metal salt solution, and the mixed metal salt solution is added dropwise to the nano-calcium carbonate suspension to adsorb the tin ions and indium ions on the surface of the polyelectrolyte modified layer;
[0020] S6, in-situ reaction coating: after the metal ion adsorption is completed, the pH value of the reaction system is controlled at 8-9, and the precipitant is added dropwise. After the addition is completed, the reaction is continued at 60-80° C. with stirring for 1.5-3 hours to obtain a conductive nano calcium carbonate suspension;
[0021] S7, post-processing step: including aging, washing and drying to obtain the final conductive nano calcium carbonate product;
[0022] S7.1, aging treatment: transferring the reaction system after the conductive tin-doped indium oxide layer coating to a sealed container for aging treatment, and standing and aging at room temperature for 10-24 hours to further stabilize and mature the generated conductive nano-calcium carbonate particles;
[0023] S7.2, washing treatment: the aged suspension is centrifuged to separate solid from liquid, and the separated solid product is washed several times with deionized water, the amount of deionized water used in each washing is 5-10 times the mass of the solid product, and the number of washing times is 3-5 times;
[0024] S7.3, Drying treatment: Place the washed conductive nano calcium carbonate wet cake in a vacuum drying oven and vacuum dry it at a temperature of 60-100°C for 4-8 hours. During the drying process, control the vacuum degree between -0.08 and 0.1 MPa to obtain a dry conductive nano calcium carbonate powder product.
[0025] Furthermore, the mass ratio of the S1 nano-calcium carbonate to deionized water is 1:5-1:10, and the mixture is stirred and dispersed at a rotation speed of 3000-5000 rpm for 20-40 minutes.
[0026] Furthermore, the S2 is added with a chitosan solution having a concentration of 0.03-0.08 mol / L according to a mass ratio of nano-calcium carbonate to chitosan of 10:1-20:1, and the stirring speed is maintained at 200-400 rpm during the dropping process. After the dropping is completed, the reaction container is placed in a constant temperature water bath, and the reaction is stirred at a temperature of 40-60°C for 1.5-2.5 hours to allow the chitosan to be fully adsorbed on the surface of the nano-calcium carbonate.
[0027] Furthermore, the S3 is dripped with a PSS polyelectrolyte solution having a concentration of 0.02-0.06 mol / L according to a mass ratio of nano-calcium carbonate to PSS polyelectrolyte of 15:1-30:1, and the stirring speed is maintained at 200-400 rpm during the dripping process.
[0028] Furthermore, in S5, the mixed metal salt solution is added dropwise to the nano-calcium carbonate suspension at a stirring speed of 300-500 rpm, the adding time is controlled within 30-60 minutes, and after the adding is completed, the mixture is stirred at 50-70° C. for 45-90 minutes.
[0029] Furthermore, the S6 is dripped with a sodium hydroxide solution with a concentration of 0.5-1.5 mol / L as a precipitant. During the process of dripping the sodium hydroxide solution, a white precipitate appears in the reaction system, that is, the tin ions and the indium ions begin to react in situ on the surface of the nano-calcium carbonate to generate conductive tin-doped indium oxide.
[0030] Compared with the prior art, the conductive nano calcium carbonate and its preparation method have the following beneficial effects:
[0031] 1. The conductive nano calcium carbonate provided by the present invention realizes the transformation of nano calcium carbonate from non-conductive to conductive by constructing a multi-layer composite structure. The conductive nano calcium carbonate not only maintains the original high specific surface area, excellent dispersibility and good biocompatibility of nano calcium carbonate, but also has good conductive properties. At the same time, the layer-by-layer assembly technology and the in-situ doping and coating technology ensure the uniformity and continuity of the conductive layer, and enhance the conductive stability of the material.
[0032] 2. The conductive nano-calcium carbonate of the present invention avoids the harmful waste gas and waste water generated in the traditional preparation process. By using environmentally friendly solvents and additives and optimizing process parameters and reaction conditions, efficient preparation and low-cost production of nano-calcium carbonate are achieved. Specifically, the preparation method of the present invention simplifies the process flow, reduces energy consumption, and reduces production costs. By precisely controlling the reaction conditions, the high quality and consistency of the product are guaranteed, which is helpful to promote the large-scale industrial application of conductive nano-calcium carbonate materials.
[0033] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 The present invention is a flow chart of the preparation method of conductive nano calcium carbonate. DETAILED DESCRIPTION
[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] Embodiment 1
[0038] This example describes in detail the preparation method of conductive nano-calcium carbonate and shows specific preparation parameters and performance test data to verify the effectiveness and superiority of the invention.
[0039] Pretreatment of nano calcium carbonate matrix: Select nano calcium carbonate raw materials with a particle size range of 20-30nm and a purity of 95%. Place it in a high-speed disperser, add deionized water, the mass ratio of nano calcium carbonate to deionized water is 1:5, and stir and disperse at a speed of 3000rpm for 20 minutes to make the nano calcium carbonate initially dispersed. Then transfer the initially dispersed suspension to an ultrasonic cleaner, and ultrasonically treat it for 30 minutes under an ultrasonic frequency of 20kHz to further break up the agglomerated nano calcium carbonate particles to obtain a uniformly dispersed nano calcium carbonate suspension. Then filter the suspension after ultrasonic treatment, and use a microporous filter membrane with a pore size of 0.2μm to remove large particle impurities that are not dispersed and other insoluble impurities that may exist. Then wash the filter cake with deionized water for multiple times until the conductivity of the washing liquid is less than 5μS / cm, ensuring that the surface of the nano calcium carbonate is clean and no impurities remain, and obtain a pretreated nano calcium carbonate dispersion.
[0040] Polyelectrolyte modified layer assembly: The pretreated nano-calcium carbonate dispersion is transferred to a reaction vessel equipped with a stirring device, a thermometer and a pH meter, and the pH value of the dispersion is accurately adjusted to 4.5 by dropping a dilute hydrochloric acid solution. Then, a chitosan solution (deacetylation degree 80%, molecular weight 50,000) with a concentration of 0.03 mol / L is slowly added according to a mass ratio of nano-calcium carbonate to chitosan of 10:1, and the stirring speed is maintained at 200 rpm during the dropping process to ensure that the chitosan solution is evenly dispersed in the nano-calcium carbonate suspension. After the dropwise addition is completed, the reaction vessel is placed in a constant temperature water bath, and the reaction is stirred at a temperature of 40°C for 1.5 hours to allow the chitosan to be fully adsorbed on the surface of the nano-calcium carbonate. After the chitosan adsorption is completed, there is no need to perform special treatment on the reaction system, and a PSS polyelectrolyte solution (molecular weight 30,000) with a concentration of 0.02 mol / L is slowly added according to a mass ratio of nano-calcium carbonate to PSS polyelectrolyte of 15:1, and the stirring speed is maintained at 200 rpm during the dropping process. After the addition was completed, the reaction was stirred at 40°C for 1 hour to allow electrostatic compounding of PSS and chitosan. This layer-by-layer assembly cycle was repeated twice, and the reaction product did not need to be separated or washed between each cycle to ensure the continuity and integrity of the modified layer.
[0041] In-situ doping and coating of conductive tin-doped indium oxide layer: The nano-calcium carbonate suspension modified by polyelectrolyte is transferred to a new reaction container, and soluble tin salt (tin chloride) and indium salt (indium chloride) are dissolved in appropriate amount of deionized water in a ratio of 0.05:1 of tin ion to nano-calcium carbonate and 0.5:1 of indium ion to nano-calcium carbonate to prepare a mixed metal salt solution. The mixed metal salt solution is slowly dripped into the nano-calcium carbonate suspension at a stirring speed of 300 rpm, and the dripping time is controlled. The reaction mixture was stirred at 50°C for 45 minutes after the addition was completed, so that the tin ions and indium ions were fully adsorbed on the surface of the polyelectrolyte modified layer. After the metal ion adsorption was completed, the reaction vessel was placed on a stirring device, and a sodium hydroxide solution with a concentration of 0.5 mol / L was slowly added as a precipitant. At the same time, the pH value of the reaction system was accurately controlled at 8. During the addition of the sodium hydroxide solution, a white precipitate gradually appeared in the reaction system, indicating that the tin ions and indium ions began to react in situ on the surface of the nano-calcium carbonate to generate conductive tin-doped indium oxide. After the addition was completed, the reaction was stirred at 60°C for 1.5 hours to ensure the full formation of the conductive layer and the uniformity of the coating.
[0042] Post-treatment: The reaction system after the completion of the conductive tin-doped indium oxide layer coating is transferred to a sealed container and aged at room temperature for 10 hours to further stabilize and mature the generated conductive nano calcium carbonate particles and improve their crystallinity and structural integrity. The aged suspension is separated into solid and liquid by centrifugation, and the separated solid product is washed multiple times with a large amount of deionized water. The amount of deionized water used in each washing is 5 times the mass of the solid product, and the number of washings is 3 times until the conductivity of the washing liquid is less than 10μS / cm, ensuring the removal of residual metal ions, sodium hydroxide and other impurities. Finally, the washed conductive nano calcium carbonate wet cake is placed in a vacuum drying oven and vacuum dried at 60°C for 4 hours to completely evaporate the water in the product to obtain a dry conductive nano calcium carbonate powder product. During the drying process, the vacuum degree is controlled between -0.08MPa to prevent oxidation or agglomeration of the product during the drying process to ensure the quality and performance stability of the product.
[0043] Performance test data: The resistivity of the conductive nano calcium carbonate prepared in this embodiment is 1.2×10 6 Ohm cm. After being immersed in a weakly acidic environment (pH = 4) for 24 hours, the mass loss rate is only 3%, indicating that it has good stability in a weakly acidic environment. When it is added to a plastic matrix (addition amount is 5%), the tensile strength of the plastic composite material is increased by 15%, and the surface resistance is increased from the original 10 12 Ohm down to 10 8 Ohm, indicating that it can effectively improve the mechanical properties of composite materials and impart certain conductive properties.
[0044] Embodiment 2
[0045] Pretreatment of nano calcium carbonate matrix: Select nano calcium carbonate raw materials with a particle size of 30-50nm and a purity of 96%. Place it in a high-speed disperser, add deionized water, and set the mass ratio of nano calcium carbonate to deionized water to 1:7. Stir and disperse at a speed of 3500rpm for 30 minutes to make the nano calcium carbonate initially dispersed. Then transfer it to an ultrasonic cleaner and ultrasonically treat it at an ultrasonic frequency of 30kHz for 45 minutes to obtain a uniformly dispersed suspension. Then filter the suspension with a microporous filter membrane with a pore size of 0.3μm to remove large particle impurities, and then repeatedly wash the filter cake with deionized water until the conductivity of the washing liquid is less than 5μS / cm to obtain a pretreated nano calcium carbonate dispersion.
[0046] Polyelectrolyte modified layer assembly: the pretreated nano-calcium carbonate dispersion is placed in a reaction container, the pH value is adjusted to 5.0 with dilute hydrochloric acid, and a chitosan solution with a concentration of 0.05 mol / L (deacetylation degree 85%, molecular weight 100,000) is slowly added according to the mass ratio of nano-calcium carbonate to chitosan of 15:1, and the stirring speed is maintained at 300 rpm during the addition. After the addition is completed, the mixture is stirred and reacted in a constant temperature water bath at 50°C for 2 hours to allow the chitosan to be fully adsorbed on the surface of the nano-calcium carbonate. After the chitosan adsorption is completed, a PSS polyelectrolyte solution with a concentration of 0.04 mol / L (molecular weight 80,000) is slowly added according to the mass ratio of nano-calcium carbonate to PSS of 20:1, and the stirring speed is 300 rpm. The mixture is stirred and reacted at 50°C for 1.5 hours to allow the PSS and chitosan to undergo electrostatic recombination. The layer-by-layer assembly cycle is repeated 3 times, and there is no need to separate or wash the reaction products in each cycle.
[0047] In-situ doping and coating of conductive tin-doped indium oxide layer: transfer the polyelectrolyte-modified nano-calcium carbonate suspension to a new container, prepare a mixed solution of tin salt (tin chloride) and indium salt (indium chloride) in a ratio of 0.1:1 by mass of tin ions to nano-calcium carbonate and 1.0:1 by mass of indium ions to nano-calcium carbonate, and slowly dropwise add the solution for 45 minutes at a stirring speed of 400 rpm. After the dropwise addition, stir at 60° C. for 60 minutes to allow the tin ions and indium ions to be fully adsorbed on the surface of the polyelectrolyte-modified layer, then slowly dropwise add a sodium hydroxide solution with a concentration of 1.0 mol / L, control the pH value of the reaction system at 8.5, and stir the reaction at 70° C. for 2 hours to allow the tin ions and indium ions to react in situ on the surface of the nano-calcium carbonate to generate conductive tin-doped indium oxide and coat it.
[0048] Post-treatment: The reaction system was aged at room temperature for 15 hours, and the aged suspension was separated into solid and liquid by a centrifuge. The separated solid was washed with deionized water for 4 times, and the amount of deionized water used each time was 7 times the mass of the solid product, until the conductivity of the washing liquid was less than 10μS / cm. Finally, the washed wet filter cake was placed in a vacuum drying oven and dried for 6 hours at 70°C and a vacuum degree of -0.09MPa to obtain a conductive nano-calcium carbonate product.
[0049] Performance test data: The resistivity of the prepared conductive nano calcium carbonate is 8.5×10 5 Ohm cm. After immersion in a weakly acidic environment (pH = 4.5) for 48 hours, the mass loss rate was 2.5%, showing good stability in a weakly acidic environment. When added to a rubber matrix (addition amount of 8%), the tensile strength of the rubber composite material increased by 20%, and the surface resistance increased from the original 10 13 Ohm down to 10 7 Ohm, effectively improving the comprehensive performance of rubber composite materials.
[0050] Embodiment 3
[0051] Pretreatment of nano calcium carbonate matrix: take nano calcium carbonate raw material with a particle size of 50-80nm and a purity of 97%, place it in a high-speed disperser, add deionized water, the mass ratio of nano calcium carbonate to deionized water is 1:10, stir and disperse at a speed of 4000rpm for 40 minutes, then transfer to an ultrasonic cleaner, ultrasonically treat at an ultrasonic frequency of 20kHz for 60 minutes to obtain a uniformly dispersed suspension, filter the suspension with a microporous filter membrane with a pore size of 0.5μm to remove impurities, and then wash the filter cake with deionized water until the conductivity of the washing liquid is less than 5μS / cm to obtain a pretreated nano calcium carbonate dispersion.
[0052] Polyelectrolyte modified layer assembly: the pretreated nano-calcium carbonate dispersion is placed in a reaction container, the pH value is adjusted to 5.5, and a chitosan solution with a concentration of 0.08 mol / L (deacetylation degree 95%, molecular weight 200,000) is slowly added dropwise according to a mass ratio of nano-calcium carbonate to chitosan of 20:1, and the stirring speed is 400 rpm during the addition. After the addition is completed, the mixture is stirred in a constant temperature water bath at 60°C for 2.5 hours to allow the chitosan to be fully adsorbed on the surface of the nano-calcium carbonate. Then, a PSS polyelectrolyte solution with a concentration of 0.06 mol / L (molecular weight 150,000) is slowly added dropwise according to a mass ratio of nano-calcium carbonate to PSS of 30:1, and the stirring speed is 400 rpm. The mixture is stirred at 60°C for 2 hours to allow the PSS and chitosan to undergo electrostatic recombination. This layer-by-layer assembly cycle is repeated 4 times, and there is no need to separate or wash the reaction products in each cycle.
[0053] In-situ doping and coating of the conductive tin-doped indium oxide layer: the polyelectrolyte-modified nano-calcium carbonate suspension is transferred to a new container, and a mixed solution of tin salt (tin chloride) and indium salt (indium chloride) is prepared and slowly added dropwise according to the mass ratio of tin ions to nano-calcium carbonate of 0.15:1 and the mass ratio of indium ions to nano-calcium carbonate of 1.5:1. The addition time is 60 minutes and the stirring speed is 500 rpm. After the addition is completed, it is stirred at 70°C for 90 minutes to allow the tin ions and indium ions to be fully adsorbed on the surface of the polyelectrolyte modified layer, and then a sodium hydroxide solution with a concentration of 1.5 mol / L is slowly added dropwise, and the pH value is controlled at 9. The reaction is stirred at 80°C for 3 hours to allow the tin ions and indium ions to react in situ on the surface of the nano-calcium carbonate to generate conductive tin-doped indium oxide and coat it.
[0054] Post-treatment: The reaction system was aged at room temperature for 24 hours, and the aged suspension was separated into solid and liquid by a centrifuge. The separated solid was washed with deionized water for 5 times, and the amount of deionized water used each time was 10 times the mass of the solid product, until the conductivity of the washing liquid was less than 10μS / cm. Finally, the washed wet filter cake was placed in a vacuum drying oven and dried for 8 hours at 100°C and a vacuum degree of -0.1MPa to obtain a conductive nano-calcium carbonate product.
[0055] Performance test data: The resistivity of the conductive nano calcium carbonate prepared in this example is 5.0×10 5 After immersion in a weak acidic environment (pH = 5) for 72 hours, the mass loss rate is only 2%, which shows excellent tolerance to weak acidic environments. When added to the coating matrix (addition amount is 10%), the washability of the coating is increased by 30%, and the surface resistance is increased from the original 10 14 Ohm down to 10 6 Ohm, significantly improving the performance of the coating.
[0056] Embodiment 4
[0057] Pretreatment of nano calcium carbonate matrix: Use nano calcium carbonate raw material with a particle size of 25-40nm and a purity of 95.5%, place it in a high-speed disperser, add deionized water, and the mass ratio of nano calcium carbonate to deionized water is 1:6. Stir and disperse at a speed of 3200rpm for 25 minutes, then transfer to an ultrasonic cleaner and ultrasonically treat at an ultrasonic frequency of 30kHz for 35 minutes to obtain a uniformly dispersed suspension. Filter the suspension with a microporous filter membrane with a pore size of 0.25μm to remove impurities, and then wash the filter cake with deionized water until the conductivity of the washing liquid is less than 5μS / cm to obtain a pretreated nano calcium carbonate dispersion.
[0058] Polyelectrolyte modified layer assembly: the pretreated nano-calcium carbonate dispersion is placed in a reaction container, the pH value is adjusted to 4.8, and a chitosan solution with a concentration of 0.04 mol / L (deacetylation degree 82%, molecular weight 60,000) is slowly added dropwise according to a mass ratio of nano-calcium carbonate to chitosan of 12:1, with a stirring speed of 250 rpm during the addition. After the addition is completed, the mixture is stirred in a constant temperature water bath at 45°C for 1.8 hours to allow the chitosan to be fully adsorbed on the surface of the nano-calcium carbonate. Then, a PSS polyelectrolyte solution with a concentration of 0.03 mol / L (molecular weight 40,000) is slowly added dropwise according to a mass ratio of nano-calcium carbonate to PSS of 18:1, with a stirring speed of 250 rpm. The mixture is stirred at 45°C for 1.2 hours to allow the PSS and chitosan to undergo electrostatic recombination. This layer-by-layer assembly cycle is repeated 2.5 times (i.e., the normal cycle is first repeated twice, and only half of the adsorption reaction process is performed for the third time), and the reaction product does not need to be separated or washed in each cycle.
[0059] In-situ doping and coating of conductive tin-doped indium oxide layer: The polyelectrolyte-modified nano-calcium carbonate suspension was transferred to a new container, and a mixed solution of tin salt (tin chloride) and indium salt (indium chloride) was prepared and slowly added dropwise according to the mass ratio of tin ions to nano-calcium carbonate of 0.08:1 and the mass ratio of indium ions to nano-calcium carbonate of 0.8:1. The addition time was 35 minutes and the stirring speed was 350 rpm. After the addition was completed, it was stirred at 55° C. for 50 minutes to allow the tin ions and indium ions to be fully adsorbed on the surface of the polyelectrolyte modified layer, and then a sodium hydroxide solution with a concentration of 0.8 mol / L was slowly added dropwise, the pH value of the reaction system was controlled at 8.2, and the reaction was stirred at 65° C. for 1.8 hours to allow the tin ions and indium ions to react in situ on the surface of the nano-calcium carbonate to generate conductive tin-doped indium oxide and coat it.
[0060] Post-treatment: The reaction system was aged at room temperature for 12 hours, and the aged suspension was separated into solid and liquid by a centrifuge. The separated solid was washed with deionized water for 3.5 times, and the amount of deionized water used each time was 6 times the mass of the solid product, until the conductivity of the washing liquid was less than 10μS / cm. Finally, the washed wet filter cake was placed in a vacuum drying oven and dried for 5 hours at 65°C and a vacuum degree of -0.085MPa to obtain a conductive nano-calcium carbonate product.
[0061] Performance test data: The resistivity of the conductive nano calcium carbonate prepared in this embodiment is 9.0×10 5 Ohm cm. After immersion in a weakly acidic environment (pH = 4.2) for 36 hours, the mass loss rate was 3.2%, showing a certain stability in a weakly acidic environment. When it was added to a plastic matrix (addition amount was 6%), the flexural strength of the plastic composite material increased by 18%, and the surface resistance increased from the original 10 11 Ohm down to 10 8Ohm, effectively improving the performance of plastic composites.
[0062] Embodiment 5
[0063] Pretreatment of nano calcium carbonate matrix: select nano calcium carbonate raw materials with a particle size of 40-60nm and a purity of 96.5%, place them in a high-speed disperser, add deionized water, the mass ratio of nano calcium carbonate to deionized water is 1:8, stir and disperse at a speed of 3800rpm for 35 minutes, then transfer to an ultrasonic cleaner, and ultrasonically treat at an ultrasonic frequency of 35kHz for 50 minutes to obtain a uniformly dispersed suspension, filter the suspension with a microporous filter membrane with a pore size of 0.35μm to remove impurities, and then wash the filter cake with deionized water until the conductivity of the washing liquid is less than 5μS / cm to obtain a pretreated nano calcium carbonate dispersion.
[0064] Polyelectrolyte modified layer assembly: the pretreated nano-calcium carbonate dispersion is placed in a reaction container, the pH value is adjusted to 5.2, and a chitosan solution (deacetylation degree 90%, molecular weight 150,000) with a concentration of 0.06 mol / L is slowly added dropwise according to a mass ratio of nano-calcium carbonate to chitosan of 18:1, and the stirring speed is 350 rpm during the dropping. After the dropping is completed, the mixture is stirred in a constant temperature water bath at 55°C for 2.2 hours to allow the chitosan to be fully adsorbed on the surface of the nano-calcium carbonate. Then, a PSS polyelectrolyte solution (molecular weight 100,000) with a concentration of 0.05 mol / L is slowly added dropwise according to a mass ratio of nano-calcium carbonate to PSS of 25:1, and the stirring speed is 350 rpm. The mixture is stirred at 55°C for 1.8 hours to allow the PSS and chitosan to undergo electrostatic recombination. This layer-by-layer assembly cycle is repeated 3.5 times (i.e., the normal cycle is performed 3 times first, and only 70% of the adsorption reaction process is performed in the fourth time), and the reaction product does not need to be separated or washed in each cycle.
[0065] In-situ doping and coating of conductive tin-doped indium oxide layer: The polyelectrolyte-modified nano-calcium carbonate suspension was transferred to a new container, and a mixed solution of tin salt (tin chloride) and indium salt (indium chloride) was prepared and slowly added dropwise according to the mass ratio of tin ions to nano-calcium carbonate of 0.12:1 and the mass ratio of indium ions to nano-calcium carbonate of 1.2:1. The addition time was 50 minutes and the stirring speed was 450 rpm. After the addition was completed, it was stirred at 65°C for 70 minutes to allow the tin ions and indium ions to be fully adsorbed on the surface of the polyelectrolyte modified layer, and then a sodium hydroxide solution with a concentration of 1.2 mol / L was slowly added dropwise, the pH value of the reaction system was controlled at 8.8, and the reaction was stirred at 75°C for 2.5 hours to allow the tin ions and indium ions to react in situ on the surface of the nano-calcium carbonate to generate conductive tin-doped indium oxide and coat it.
[0066] Post-treatment: The reaction system was aged at room temperature for 18 hours, and the aged suspension was separated into solid and liquid by a centrifuge. The separated solid was washed with deionized water for 4.5 times, and the amount of deionized water used each time was 8 times the mass of the solid product, until the conductivity of the washing liquid was less than 10μS / cm. Finally, the washed wet filter cake was placed in a vacuum drying oven and dried for 7 hours at 80°C and a vacuum degree of -0.095MPa to obtain a conductive nano calcium carbonate product.
[0067] Performance test data: The resistivity of the conductive nano calcium carbonate prepared in this embodiment is 6.5×10 5 Ohm cm. After immersion in a weakly acidic environment (pH = 4.8) for 60 hours, the mass loss rate was 2.8%, showing good stability in a weakly acidic environment. When added to a rubber matrix (addition amount was 7%), the tear strength of the rubber composite material increased by 22%, and the surface resistance increased from the original 10 12 Ohm down to 10 7 Ohm, significantly improving the performance of rubber composites.
[0068] Comparative Example
[0069] In this comparative example, conductive nano-calcium carbonate was prepared by a conventional direct mixing method. Ordinary nano-calcium carbonate (particle size 50 nm, purity 95%) without any modification was directly mixed with conductive powder (tin oxide) in a high-speed stirrer at a stirring speed of 2000 rpm for 30 minutes. The mass ratio of nano-calcium carbonate to conductive powder was 9:1.
[0070] Performance test data: The resistivity of the prepared mixture is as high as 5.0×10 8 Ohm cm, after being immersed in a weakly acidic environment (pH = 4.5) for 12 hours, the mass loss rate reached 15%. When it was added to the plastic matrix (addition amount was 6%), the tensile strength of the plastic composite material was only increased by 5%, and the surface resistance was only reduced to 10 10 Compared with the embodiments of the present invention, the conductivity, stability in a weakly acidic environment and the effect of improving the performance of the composite material are all poor, which fully demonstrates the advantages of the present invention in preparing conductive nano calcium carbonate.
[0071] The performance of the conductive nano calcium carbonate prepared in Example 1, Example 2, Example 3, Example 4, Example 5 and the comparative example was tested, and the results are shown in the following table:
[0072]
[0073]
[0074] As shown in the table above, through the analysis of the performance test results of each embodiment and the comparative example, it can be seen that the conductive nano calcium carbonate prepared by the present invention exhibits excellent performance. In terms of resistivity, embodiments one to five are significantly lower than the comparative example, reflecting that the present invention effectively reduces the resistivity of the material to achieve good conductive performance; in terms of stability in a weakly acidic environment, the mass loss rate of each embodiment after soaking for a certain period of time is controlled at a low level; for the improvement of composite material performance, adding to different matrices has a positive effect, while the comparative example has a weak effect on the performance improvement of the plastic matrix. The conductive nano calcium carbonate of the present invention has excellent performance in many aspects such as conductivity, stability and reinforcement of composite materials, and has broad application prospects and great practical value.
[0075] In summary, the conductive nano-calcium carbonate of the present invention performs well in various key performance indicators, has obvious innovation and superiority compared with traditional structures, has broad application prospects and huge market potential in the field of nanomaterials, and is expected to bring significant performance improvements and breakthroughs to related products.
[0076] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. Conductive nano calcium carbonate, characterized in that: The conductive nano calcium carbonate has a multi-layer composite structure, including a nano calcium carbonate matrix, a polyelectrolyte modified layer located on the surface of the matrix, and a conductive tin-doped indium oxide layer coated on the modified layer, specifically: The polyelectrolyte modified layer is formed by assembling positively charged chitosan and negatively charged PSS polyelectrolyte on the surface of the nano calcium carbonate matrix, wherein: The positively charged chitosan is selected to have a deacetylation degree of 80%-95%, the pH value of the nano-calcium carbonate dispersion is adjusted and the chitosan solution is added, so that the chitosan is uniformly adsorbed on the surface of the nano-calcium carbonate matrix through electrostatic attraction to form a preliminary modified layer; After the chitosan is adsorbed, the negatively charged PSS polyelectrolyte solution is added to the reaction system to allow the PSS and chitosan to undergo electrostatic recombination, and the layer-by-layer assembly cycle operation is repeated 2-4 times to allow the PSS and chitosan to be alternately adsorbed to form a multi-layer polyelectrolyte modified layer; The conductive tin-doped indium oxide layer dissolves soluble tin chloride and indium chloride and reacts with the nano-calcium carbonate suspension to form a uniform conductive layer.
2. The conductive nano calcium carbonate according to claim 1, characterized in that: The concentration of the positively charged chitosan during the assembly process is controlled at 0.03-0.08 mol / L, and the pH value of the nano-calcium carbonate dispersion is adjusted to 4.5-5.
5. After the chitosan solution is added, stirring is performed at a temperature of 40-60° C. for 1.5-2.5 hours.
3. The conductive nano calcium carbonate according to claim 1, characterized in that: The concentration of the negatively charged PSS polyelectrolyte solution is controlled at 0.02-0.06 mol / L and stirred at a temperature range of 40-60° C. for 1-2 hours.
4. The conductive nano calcium carbonate according to claim 1, characterized in that: The conductive tin-doped indium oxide layer is composed of tin ions Sn2+ and indium ions In3 and oxygen ions O 2 - The tin-doped indium oxide ITO generated by the reaction, wherein the molar ratio of tin ions to indium ions is 1:8-1:12, the mass ratio of tin ions to nano-calcium carbonate is 0.05-0.15:1, and the mass ratio of indium ions to nano-calcium carbonate is 0.5-1.5:
1.
5. A method for preparing conductive nano calcium carbonate, applicable to the conductive nano calcium carbonate described in any one of claims 1 to 4, characterized in that: The specific steps of the preparation method are: S1. Pretreatment of nano calcium carbonate matrix: using nano calcium carbonate as raw material, placing the nano calcium carbonate raw material in a high-speed disperser, adding deionized water as a dispersion medium for stirring and dispersion, so that the nano calcium carbonate is initially dispersed to form a suspension; S2, ultrasonic treatment: the suspension after preliminary dispersion is transferred to an ultrasonic cleaner, and ultrasonically treated for 30-60 minutes at an ultrasonic frequency of 20-40kHz to break up the agglomerated nano-calcium carbonate particles to obtain a uniformly dispersed nano-calcium carbonate suspension, and the suspension after ultrasonic treatment is filtered, and the filter cake is washed with deionized water for multiple times to obtain a pre-treated nano-calcium carbonate dispersion; S3, polyelectrolyte modified layer assembly: adding sodium hydroxide solution to the pretreated nano-calcium carbonate dispersion to adjust the pH value of the dispersion to 4.5-5.5, and adding chitosan solution to make the chitosan solution uniformly dispersed in the nano-calcium carbonate suspension; S4, PSS adsorption and layer-by-layer assembly cycle: After the chitosan adsorption is completed, the PSS polyelectrolyte solution is added dropwise, and stirring is continued during the dropping process. After the dropping is completed, stirring and reacting at 40-60°C for 1-2 hours to allow PSS and chitosan to undergo electrostatic compounding. The layer-by-layer assembly cycle operation is repeated 2-4 times to finally obtain a polyelectrolyte-modified nano-calcium carbonate suspension; S5, in-situ doping and coating of the conductive tin-doped indium oxide layer: the nano-calcium carbonate suspension modified by the polyelectrolyte is subjected to metal ion adsorption, and soluble tin chloride and indium chloride are dissolved in deionized water in a ratio of 0.05-0.15:1 of tin ions to nano-calcium carbonate and 0.5-1.5:1 of indium ions to nano-calcium carbonate to prepare a mixed metal salt solution, and the mixed metal salt solution is added dropwise to the nano-calcium carbonate suspension to adsorb the tin ions and indium ions on the surface of the polyelectrolyte modified layer; S6, in-situ reaction coating: after the metal ion adsorption is completed, the pH value of the reaction system is controlled at 8-9, and the precipitant is added dropwise. After the addition is completed, the reaction is continued at 60-80° C. with stirring for 1.5-3 hours to obtain a conductive nano calcium carbonate suspension; S7, post-processing step: including aging, washing and drying to obtain the final conductive nano calcium carbonate product; S7.1, aging treatment: transferring the reaction system after the conductive tin-doped indium oxide layer coating to a sealed container for aging treatment, and standing and aging at room temperature for 10-24 hours to further stabilize and mature the generated conductive nano-calcium carbonate particles; S7.2, washing treatment: the aged suspension is centrifuged to separate solid from liquid, and the separated solid product is washed several times with deionized water, the amount of deionized water used in each washing is 5-10 times the mass of the solid product, and the number of washing times is 3-5 times; S7.3, Drying treatment: Place the washed conductive nano calcium carbonate wet cake in a vacuum drying oven and vacuum dry it at a temperature of 60-100°C for 4-8 hours. During the drying process, control the vacuum degree between -0.08 and 0.1 MPa to obtain a dry conductive nano calcium carbonate powder product.
6. The method for preparing conductive nano calcium carbonate according to claim 6, characterized in that: The mass ratio of the S1 nano-calcium carbonate to deionized water is 1:5-1:10, and the mixture is stirred and dispersed at a rotation speed of 3000-5000 rpm for 20-40 minutes.
7. The method for preparing conductive nano calcium carbonate according to claim 6, characterized in that: The S2 is added with a chitosan solution having a concentration of 0.03-0.08 mol / L according to a mass ratio of nano-calcium carbonate to chitosan of 10:1-20:1, and the stirring speed is maintained at 200-400 rpm during the dropping process. After the dropping is completed, the reaction container is placed in a constant temperature water bath, and the reaction is stirred at a temperature of 40-60°C for 1.5-2.5 hours to allow the chitosan to be fully adsorbed on the surface of the nano-calcium carbonate.
8. The method for preparing conductive nano calcium carbonate according to claim 6, characterized in that: The S3 is added dropwise with a PSS polyelectrolyte solution having a concentration of 0.02-0.06 mol / L according to a mass ratio of nano-calcium carbonate to PSS polyelectrolyte of 15:1-30:1, and the stirring speed is maintained at 200-400 rpm during the dropping process.
9. The method for preparing conductive nano calcium carbonate according to claim 6, characterized in that: In S5, the mixed metal salt solution is added dropwise to the nano-calcium carbonate suspension at a stirring speed of 300-500 rpm, the adding time is controlled within 30-60 minutes, and after the adding is completed, the mixture is stirred at 50-70° C. for 45-90 minutes.
10. The method for preparing conductive nano calcium carbonate according to claim 6, characterized in that: The S6 is dripped with a sodium hydroxide solution with a concentration of 0.5-1.5 mol / L as a precipitant. During the addition of the sodium hydroxide solution, a white precipitate appears in the reaction system, that is, tin ions and indium ions begin to react in situ on the surface of the nano-calcium carbonate to generate conductive tin-doped indium oxide.